Perampanel and childhood absence epilepsy: A real life experience - Operto, Francesca Felicia; Orsini, Alessandro; Sica, Gianpiero; Scuoppo, Chiara; Padovano, Chiara; Vivenzio, Valentina; de Simone, Valeria; Rinaldi, Rosetta; Belfiore, Gilda; Mazza, Roberta; Aiello, Salvatore; Vetri, Luigi; et al. (Frontiers in Neurology, 2022)
Objectives: The aim of our study was to evaluate the effectiveness and tolerability of perampanel (PER) as first add-on and as second line monotherapy in subjects with childhood absence epilepsy. Methods: Our sample consisted of 20 patients with childhood absence epilepsy, aged between 8-10, already in therapy with a first antiseizure medication with incomplete seizure control. PER was added as first add-on in a dose ranging from 3-8 mg/die with 1- 2 mg/week increments. The patients that were seizure-free were shifted to a PER monotherapy. All patients underwent a standardized neuropsychological evaluation in order to assess non-verbal intelligence and executive functions before adding PER and after 6 months of drug therapy. All parents completed two questionnaires, in order to assess the emotional-behavioral problems and parental stress. Results: 15/20 patients responded to add-on PER and were seizure-free, in 3/20 patients we observed a reduction of seizure frequency <50%, and in the 2 remaining patients the add-on therapy with PER did not lead to a reduction in seizures frequency from baseline. The patients who were seizure-free were switched to PER monotherapy. 9/15 patients remained seizure-free in monotherapy with PER. In the first month of therapy with PER 2/20 patients (10%) reported mild, transient side effects of irritability, headache and dizziness, which did not lead to discontinuation of therapy. Adjunctive treatment with PER did not negatively affect non-verbal intelligence, executive functions, emotional/behavioral symptoms of children and parental stress levels. Significance: Our clinical experience in real life showed that PER appears to be effective in the control of absence seizures in childhood absence epilepsy, with a favorable tolerability profile. PER would seem effective on absence seizures even in monotherapy. Further studies with larger samples, longer follow-up and controlled versus placebo (or other first choice antiseizure medications) are needed to confirm our data.